Intermittent supplementation of Spirulina platensis: effects on post-peak laying hen performance, protein digestibility, physiological responses, and egg quality - Agusetyaningsih, I.; Luthfian, F.; Widiastuti, E.; Wahyuni, H. I.; Yudiarti, T.; Sari, D. A. P.; Sugiharto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study evaluated the effects of different frequencies of Spirulina platensis S. platensis )supplementation on blood parameters, protein digestibility, fecal characteristics, egg quality, and production performance in laying hens. A total of 224 ISA Brown hens (55 weeks old, BW ±1907 g) were assigned to four groups: T0 (control, basal feed), T1 (0.5% S. platensis daily), T2 (0.5% every other day), and T3 (0.5% twice a week). The trial lasted for eight weeks, with weekly measurements of feed intake, egg production, and egg quality. Blood was collected at the end of the experiment to assess hematological profiles, while fecal samples were analyzed for protein digestibility and nitrogen excretion. Results showed that T3 and T4 significantly increased red blood cell count, hemoglobin concentration, hematocrit value, and leukocyte count compared to the control (P<0.05). Compared to T0, nitrogen retention and protein digestibility coefficients (%) in T1, T2, and T3 were significantly different (P<0.05). Excretory nitrogen levels in the treatment groups (T1, T2, and T3) were substantial-ly lower than those in T0 (P<0.05). Compared to T0, fecal ammonia levels in the treatment groups (T1, T2, and T3) were lower. The water content in T3 was significantly higher than that in T2 (P<0.05). Haugh Unit values in T1 and T2 were significantly higher than those in T0 and T3 (P<0.05). HDP at weeks 6 and 12 in T1, T2, and T3 were significantly higher than those in T0 (P<0.05). In conclusion, S. platensis supplementation enhanced hematological status, nutrient utilization, fecal characteristics, egg quality, and production performance. Twice-weekly supplementation (T3) was as effective as the more frequent regimens, suggesting a practical and cost cost-efficient strategy for laying hens.